Optimisation of medium formulation and scaling up of threonine and tryptophan production by lactic acid bacteria using response surface methodology - Lim, Ye Heng (2017)
Increasing knowledge on the functions of amino acid (AA) in animal production has led to escalating demand of various amino acid. Threonine and tryptophan are among the most commonly employed feed AA due to their indispensable roles in enhancing the growth performance of livestocks. Currently, AA production relies heavily on non-food-grade-microorganisms such as genetically modified Corynebacterium glutamicum and Escherichia coli which was a concern as the use of genetically modified C. glutamicum for production of amino acid was linked to over thousand cases of a deadly syndrome, eosinophila myalgia syndrome (EMS). This has urged for search of safer alternatives by utilising food-grade-microorganisms. Recent studies reported that lactic acid bacteria (LAB) were capable to produce various AA owing to their well-established proteolytic system and presence of AA biosynthesis gene. Furthermore, they are reputed with the Generally Recognised as Safe (GRAS) status, making them an excellent candidate as food grade producer. However, there were limited studies regarding production of AA by using LAB. Hence, the objective of this study was to identify the threonine and tryptophan producing LAB and optimise the medium formulation via response surface methodology (RSM) approach, followed by scaling up their production by using constant impeller tip speed approach. It was hypothesised that threonine and tryptophan producing LAB could be identified and their production could be improved by optimisation of the medium formulation using RSM. Additionally, the production of threonine and tryptophan by the selected LAB could be scaled up constant impeller tip speed approach. In this study, 17 LAB isolates from Malaysian foods were identified phenotypically and genotypically. The isolates comprised of 3 species: Pediococcus pentosaceus (6 isolates), Pediococcus acidilactici (2 isolates), and Lactobacillus plantarum (9 isolates). Thereafter, the growth profile of the isolates were characterised and their proteolytic activity was determined qualitatively and quantitatively under 3 pH conditions by using skim milk agar hydrolysis assay, skim milk agar well diffusion assay and azocasein assay due to the important role of proteolytic activity on amino acid production. All the LAB isolates exhibited versatile extracellular proteolytic system where proteolytic activity was detected over wide pH range. The highest extracellular proteolytic activity at pH 5 (15.76 U/mg) and pH 8 (19.42 U/mg) was detected in L. plantarum RG14. Meanwhile, L. plantarum RS5 and RI11 demonstrated the highest extracellular proteolytic activity of approximately 17 U/mg at pH 6.5. The ability of the LAB isolates to produce AA was subsequently determined by cultivating in de Man Rogosa and Sharpe (MRS) medium. The production of amino acid was quantified by using high performance liquid chromatography (HPLC) analysis. The LAB isolates demonstrated the ability to produce numerous industrially important AA but the production was strain dependent. P. pentosaceus TL-3 demonstrated highest threonine productivity (12.88 mg/L/h) and identified as superior threonine producer in this study. Meanwhile, P. acidilactici TP-6 was selected as tryptophan producer with a productivity of 5.05 mg/L/h. The production of threonine and tryptophan by the selected LAB isolate was subsequently optimised by using RSM. The nutritional requirement for threonine and tryptophan production was first evaluated by using Plackett Burman Design (PBD) and subsequently optimised by using Central Composite Design (CCD). Molasses, meat extract, (NH4)2SO4 and MnSO4 were the most important components for threonine production by P. pentosaceus TL-3 with an optimum concentration of 30.79 g/L, 25.30 g/L, 8.59 g/L, and 0.098 g/L respectively. The net threonine produced recorded by P. pentosaceus TL-3 under optimised condition (125.98 mg/L) was improved by 2 fold whereas the cost of the optimised medium was reduced by 8.5% compared to MRS medium. In comparison, the best combination of medium components for tryptophan production by P. acidilactici TP-6 were molasses, meat extract, urea and FeSO4. The optimum concentration suggested by RSM were: molasses, 14.06 g/L; meat extract 23.68 g/L; urea, 5.56 g/L and FeSO4, 0.024 g/L. Up to 68.05 mg/L of tryptophan was produced by P. acidilactici TP-6 under optimised condition, which was equivalent to 150% enhancement compared to the control. In contrast, the cost of the optimised medium was reduced by 11%. Furthermore, the production of threonine and tryptophan by the selected LAB isolate was successfully scaled up in 30 L stirred tank bioreactor based on constant impeller tip speed approach. Additionally, the net threonine and tryptophan produced in bioreactor cultivation was comparable to the predicted amount suggested by CCD. In conclusion, P. pentosaceus TL-3 and P. acidilactici TP-6 were identified as threonine and tryptophan producer respectively and the production of threonine and tryptophan by the selected producer strain was enhanced by 2 folds and 150% respectively through optimisation of their medium formulation using RSM approach. Additionally, the production of threonine and tryptophan was successfully scaled by based on constant impeller tip speed approach where the production in both small and large scale cultivation was comparable.